IMPLEMENTATION OF REGENT REGULATION NUMBER 74 OF 2018 ON POLICIES AND STRATEGIES FOR THE MANAGEMENT OF HOUSEHOLD WASTE AND HOUSEHOLD-LIKE WASTE IN JUMBA VILLAGE, AMUNTAI SELATAN DISTRICT, HULU SUNGAI UTARA REGENCY - supiatunnisa supiatunnisa; Agus Surya Dharma; Anna Maryati (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Household waste management is a critical environmental issue due to its direct impact on public health, cleanliness, and quality of life. In Jumba Village, South Amuntai District, Hulu Sungai Utara Regency, the implementation of Regent Regulation Number 74 of 2018 concerning Waste Management Policy and Strategy has not been optimally carried out. This study aims to analyze the implementation of the regulation and identify supporting and inhibiting factors at the village level. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving 13 informants selected using purposive sampling. Data analysis was conducted through credibility testing, including prolonged engagement, triangulation, and member checking. The results indicate that the implementation of waste management policy has not been effective. This is reflected in the low level of community participation and compliance in waste sorting, weak coordination among stakeholders, limited resources, and inadequate policy socialization. Supporting factors include the role of community leaders and the availability of waste collection officers, while inhibiting factors consist of low public awareness and budget constraints. This study concludes that strengthening coordination, improving policy socialization, and enhancing community participation are essential to improving the effectiveness of household waste management policy implementation at the village level.